Timing and Temporality in Islamic Philosophy and Phenomenology of Life - Tymieniecka, Anna-Teresa (Islamic Philosophy and Occidental Phenomenology in Dialogue, 2007)
From time immemorial, concern with timing of life has been crucial for the regulation of human praxis as well as for the philosophical quest to understand existence by seeking its meaning. The two used to inform each other, until modernity, when they parted. In spite of the extensive progress in manipulating change and motion, and of the abundance of metaphysical attempts to enlighten human beings about their fate, the puzzling nature of temporality and timing of reality remains controversial. The present collection of studies seeks a new answer by initiating a novel investigation informed by the ancient wisdom of the Greaco-Arabic-Islamic sources and inheritance, on the one side, and the contemporary discernment of Occidental phenomenology of life, on the other, in a common dialogical effort to unravel this great enigma of existence. Papers by: Anna-Teresa Tymieniecka, William C. Chittick, Reza Akbarian, Daniela Verducci, Michael F. Andrews, Seyyed Mohammed Khamenei, Nader El-Bizri, Mehdi Aminrazavi, Massimo Durante, Abdul Rahim Afaki, Maria-Chiara Teloni, A.L. Samian, Kathleen Haney, Jad Hatem, Robert J. Dobie, Michel Dion.